STUDY OF PAULO FREIRE'S THOUGHTS AS A REFORMULATION OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM IN THE DIGITALIZATION ERA - Khoirul Huda; Muhammad Najihul Huda; Syarof Nursyah Ismail (Widya Balina, 2025)
The rapid development of technology in the digital era has brought significant changes in various aspects of life, including in the world of education. Islamic Religious Education (PAI) is no exception, facing the challenge of remaining relevant and effective in shaping students' personality characters. The current PAI curriculum is considered not fully able to accommodate the needs of the times that demand the integration of Islamic values ​​with digital competencies. The urgency of reformulating the PAI curriculum is very important in order to create an adaptive, innovative, and future-oriented learning model. This study aims to express constructive ideas in reformulating the PAI curriculum by referring to Paulo Freire's thoughts, while the method used is qualitative based on literature studies. In the end, this study concluded that the reformulation of the PAI curriculum can be realized by adopting the theory of integrity-reality initiated by Paulo Freire, the integrity-reality in question is integrating Islamic values ​​and the sophistication of digital technology. Reformulation of the PAI curriculum can be done by continuing to place the source of Islamic teachings as a fundamental rule, and placing humans as the main center in science. In other words, digital technology is only used as a limited tool in learning and teaching methods.